2020
DOI: 10.2147/ott.s252043
|View full text |Cite
|
Sign up to set email alerts
|

<p>Ribosome Binding Protein 1 Correlates with Prognosis and Cell Proliferation in Bladder Cancer</p>

Abstract: Introduction Ribosome binding protein 1 (RRBP1) is reported to be correlated with tumor formation and progression. However, the role of RRBP1 in bladder cancer is unclear. In this study, we aimed to investigate the expression of RRBP1 and its influence on cell proliferation in bladder cancer. Methods Quantification real-time polymerase chain reaction (qRT-PCR) and immunohistochemistry (IHC) were used to detect the expression levels of RRBP1 in 138 bladder cancer and mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Forty-eight hours after transfection of the shRRBP1 plasmid targeting BFTC909, both mRNA and protein expression levels were inhibited (Figure 4F). RRBP1 was previously associated with cell proliferation [35]. In the present study, WST-1 analysis performed 48 h after transfection of shRRBP1 with BFTC909 showed that RRBP1 was inhibited and cell proliferation was reduced (Figure 4H).…”
Section: Rrbp1 Is Highly Expressed In Utuc Tumor Tissues and Cancer Cell Lines Of Urothelial Tumorssupporting
confidence: 66%
See 1 more Smart Citation
“…Forty-eight hours after transfection of the shRRBP1 plasmid targeting BFTC909, both mRNA and protein expression levels were inhibited (Figure 4F). RRBP1 was previously associated with cell proliferation [35]. In the present study, WST-1 analysis performed 48 h after transfection of shRRBP1 with BFTC909 showed that RRBP1 was inhibited and cell proliferation was reduced (Figure 4H).…”
Section: Rrbp1 Is Highly Expressed In Utuc Tumor Tissues and Cancer Cell Lines Of Urothelial Tumorssupporting
confidence: 66%
“…The upregulated expression of RRBP1 in lung cancer, colorectal cancer, endometrial endometrioid adenocarcinoma, ovarian, breast, and bladder cancer leads to poor prognosis [22,26,29,30,35,40]. The inhibited expression of RRBP1 could potentially reduce the proliferation and metastasis of cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…In our patient, two ALK fusion partners ( RRBP1 , HAO1 ) were detected simultaneously by RNA-seq. RRBP1 is an ER membrane protein in the secretion and transportation of nascent proteins in mammalian cells ( 8 ). RRBP1 overexpression has been confirmed to be associated with poor prognosis and an independent predictor of overall survival (OS) and disease-free survival (DFS) in other cancers, for example, epithelial ovarian cancer ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…RRBP1 overexpression has been confirmed to be associated with poor prognosis and an independent predictor of overall survival (OS) and disease-free survival (DFS) in other cancers, for example, epithelial ovarian cancer ( 9 ). It is due to that RRBP1 overexpression can promote tumor cell proliferation ( 8 ). In our case, the 3' end of ALK exon 19 fused to the 5' end of RRBP1 exon 10.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, RRBP1 has been identified as an important oncogenic factor to induce tumorigenesis and malignant progression. RRBP1 is reported to be highly expressed in multiple cancers and may serve as a potential biomarker for prognostic prediction [ 27 , 28 , 29 , 32 , 47 , 48 ]. Although several studies have shown that the enhanced RRBP1 expression in tumor cells is attributed to its transcriptional and translational activation [ 49 , 50 , 51 ], nothing is known about whether RRBP1 can be regulated at post‐translational level.…”
Section: Discussionmentioning
confidence: 99%